Design estratégico em tempos de mídias sociais: um estudo sobre a geração digital como fonte para projetos de design - Corrêa, Marcelo Barbosa (Universidade do Vale do Rio dos Sinos, 2014)
This exploratory research is the understanding the Digital Generation, in order to promote information sources for design project’s briefings focused on an audience that sees the Internet to build their sociability. In light of the Strategic Design, is intended to identify what are the theories that define this generation to propose ways for more effective communication between young and project team, enhancing the opportunities for innovation in the delivery. As a starting point, was made a Literature Review and a Systematic Review of articles published in Capes seeking to identify the relevant theoretical treatises on the subject, featuring Digital Generation. Later of these preliminary steps were developed a projetual exercise in order to get four scenarios that represent forms of communication between the Digital Generation and a project team through the construction of scenarios, based on the Reyes model (2010). The four scenarios resulting from the process were the inspiration for proposing a set of guidelines for companies seeking innovation through interaction with young consumers. As a result, were designed four projectual paths, which showed how common element the ubiquity of the Internet in the processes of design and put social networking as a facilitator of dialogue between the actors.
Keywords: Design estratégico; Geração digital; Redes sociais; Interação comunicacional; Strategic design; Digital generation; Social networks; Communicational interaction; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial